Peran Fasilitator Pendamping BTPN Syariah dalam Mengembangkan Identitas Merek dan Dampaknya Terhadap Penjualan Produk di MMS Bakung - Syamroxy; Iryanti, Endang (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
Brand identity is an element that shapes the way a brand looks, feels and communicates with its audience. This research further studies the role of BTPN Syariah facilitator in developing brand identity and its impact on product sales at MMS Bakung. This research aims to (1) Know the role of the facilitator companion (2) Know the impact of using brand identity on sales growth at MMS Bakung. The research method used is qualitative method, through direct interviews with BTPN Syariah customers. The results of this study show (1) The role of BTPN Syariah facilitators in developing brand identity is to plan and guide the creation of business identity and implement it in daily business activities, and (2) The impact of using brand identity on sales at MMS Bakung is experiencing an increase in sales/customers although not significant. Keywords: Identity, Brand, Facilitator.